Morphopragmatic Interference between the Nias Language and Slang in Junior High School Students’ Language Use: A Study at SMP Negeri 1 Lahewa: Dinamika Interferensi Morfopragmatik Bahasa Nias dan Bahasa Gaul pada Bahasa Siswa SMP Negeri 1 Lahewa - Selianus Baeha; Friska Ria Sitorus; Firaman Gula; Honoratus Irpan Sinurat (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
This study examines morphopragmatic interference arising from the interaction of the Nias language, Indonesian, and slang among students at SMP Negeri 1 Lahewa. It focuses on identifying patterns of morphological and pragmatic interference and applies a Deep Learning approach to map linguistic features in students’ language use. A descriptive qualitative method was employed. Data were collected from students’ spoken utterances and written texts derived from school assignments and communication media. The data were manually labeled to identify morphological and pragmatic elements, then analyzed using Deep Learning models to detect patterns of language interference. The findings reveal multiple forms of interference. Morphological interference appears in the use of Nias affixes within Indonesian and slang vocabulary, while pragmatic interference is reflected in shifts in speech functions influenced by students’ sociocultural backgrounds. The study concludes that such interference represents students’ social identities and highlights the need for pedagogical attention in Indonesian language instruction.